Change and Tradition: New Haven, Connecticut, 1780-1830 - Philie, William L. (Garland Pub., 1989)
Keywords: 18th century; Elite (Social sciences); 18th century; Urbanization; 19th century; New Haven (Conn.); 19th century; Urbanization; Connecticut; Economic conditions; Elite (Social sciences); History; New Haven; Politics and government; New Haven (Conn.); dept.aa; faculty_collection

An antipredation mechanism of the polychaete Phyllodoce mucosa with notes on similar mechanisms in other potential prey - Prezant, Robert S. (Fishery Bulletin, 1980)
Keywords: dept.aa; ⛔ No DOI found

Functional ultramorphology of the dissoconch valves of the oyster Crassostrea virginica - Carriker, Melbourne R.; Palmer, Robert E.; Prezant, Robert S. (Proceedings-National Shellfisheries Association (USA), 1980)
Keywords: dept.aa; ⛔ No DOI found

The arenophilic radial mantle glands of the Lyonsiidae (Bivalvia: Anomalodesmata) with notes on lyonsiid evolution - Prezant, R. S. (Malacologia, 1981)
Keywords: dept.aa; ⛔ No DOI found

Comparative shell ultrastructure of lyonsiid bivalves - Prezant, Robert S. (The Veliger, 1981)
Keywords: dept.aa; ⛔ No DOI found

Taxonomie Re-Evaluation of the Bivalve Family Lyonsiidae - Prezant, Robert S. (The Nautilus, 1981)
Keywords: dept.aa; ⛔ No DOI found

Shell microstructure of Corbicula fluminea (Bivalvia: Corbiculidae) - Counts, C. L.; Prezant, R. S. (The Nautilus, 1982)
Keywords: dept.aa; ⛔ No DOI found

Functional microstructure of the lithodesma of mytilimeria nuttalli (bivalvia: anomalodesma) - Prezant, R. S.; Carriker, M. R. (The Veliger, 1983)
Keywords: dept.aa; ⛔ No DOI found

Auto-drilling in the oyster drill Thais haemastoma (Muricidae) - Prezant, R. S. (The Nautilus, 1983)
Keywords: dept.aa; ⛔ No DOI found

Functional microstructure and mineralogy of the byssal complex of Anomia simplex orbigny (Bivalvia: Anomiidae) - Prezant, Robert S. (American Malacological Bulletin, 1984)
Keywords: dept.aa; ⛔ No DOI found

Flotation of the bivalve Corbicula fluminea as a means of dispersal - Prezant, Robert S.; Chalermwat, Kashane (Science, 1984)
75 citations (Crossref) [2023-10-31]
Keywords: dept.aa

Comparative shell microstructure of North American Corbicula (Bivalvia: Sphaeriacea) - Prezant, Robert S.; Tan-Tiu, Antonieto (The Veliger, 1985)
Keywords: dept.aa; ⛔ No DOI found

Molluscan mucins: a unifying thread - Prezant, Robert S. (American Malacological Bulletin Special Issue, 1985)
Keywords: dept.aa; ⛔ No DOI found

Derivations of arenophilic mantle glands in the Anomalodesmata - Prezant, R. S. (Malacologia, 1985)
Keywords: dept.aa; ⛔ No DOI found

Occurrence of a digenetic trematode in a polychaete - Brown, B; Prezant, R. S. (Journal of Invertebrate Pathology, 1986)
5 citations (Crossref) [2023-10-31]
Keywords: dept.aa

Entrainment of larval oysters by hydraulic cutterhead dredges: An introduction - Prezant, R. S. (Entrainment of Larval Oysters, American Malacological Bulletin, 1986)
Keywords: dept.aa; ⛔ No DOI found

Spiral Crossed-Lamellar Shell Growth in Corbicula (Mollusca: Bivalvia) - Prezant, Robert S.; Tiu, Antonieto Tan (Transactions of the American Microscopical Society, 1986)
Spiral and near-spiral growth patterns of the peripheral crossed-lamellar shell microstructure of the bivalve Corbicula cf. fluminea have been discovered. This is the first report of spiral microstructures outside of nacreous and "foliated calcite" deposits. The spiral growth surface in this corbiculid is underlain by a conical crossed-lamellar microstructure. This form of lath deposition is usually associated with high concentrations of organic material located beneath the undertucked periostracum along the valve's periphery. These structures can offer the bivalve additional resistance against predators that enter the valves through the shell's edge. Similar spiral structures have not been found in all "white" forms of North American Corbicula, in the "purple" form of North American Corbicula, nor in the corbiculids Polymesoda caroliniana and P. (Geloina) erosa.
3 citations (Crossref) [2023-10-31]
Keywords: dept.aa

Shell microstructure responses of the Atlantic ribbed mussel Geukensia demissa granosissima induced by transplantation. - Tiu, A.; Prezant, Robert (American Malacological Bulletin, 1987)
Keywords: dept.aa; ⛔ No DOI found

Shell microstructure and color changes in stressed Corbicula fluminea (Bivalvia: Corbiculidae) - Prezant, Robert S.; Tiu, A. Tan; Chalermwat, Kashane (The Veliger, 1988)
Keywords: dept.aa; ⛔ No DOI found

Seasonal variation of microstructure of inner structure of shell in Corbicula fluminea (Bivalvia: Heterodonta). - Tan Tiu, A; Prezant, R. (American Malacological Bulletin, 1989)
Keywords: dept.aa; ⛔ No DOI found

Shell tubules in Corbicula fluminea (Bivalvia: Heterodonta): functional morphology and microstructure - Tan Tiu, A; Prezant, R. S. (Shell tubules in Corbicula fluminea (Bivalvia: Heterodonta): functional morphology and microstructure, 1989)
Place: Sanibel, FL
Keywords: dept.aa; ⛔ No DOI found